(untitled) (Heritage, 2025)
This comprehensive review outlines the central role of formal education in cultural and national identity management and emphasizes the interdependence and synergy between culture and education. The study affirms the benefits of integrating cultural and national identity themes into the curriculum that promote critical thinking, tolerance and inclusivity. Through the study of history, language, the arts, collaboration with cultural institutions, organisation of cultural events or paying a visit to cultural sites, education can contribute to the understanding and preservation of cultural and national heritage. The report offers illuminating insights into real-life examples from around the world. It also highlights the need for a balanced and nuanced approach that addresses the challenges of globalization, diverse ethnic structures, and the coexistence of national and global citizenship education. Ultimately, the study argues that education is a powerful tool for the preservation of cultural and national heritage, both to preserve cultural heritage and to promote unity, social awareness and global respect.